(untitled) (Journal of Parents and Teachers, 2023)
The concept of "quality" is abstract and gives allows to different centers seeking different objectives according to their conception. For this reason, the article reflects on this concept and presents 6 paradigms of educational quality. Finally, it analyzes the importance of center evaluation as a fundamental tool.